Between Sharia and Trend: The Relevance of Hadith on Muslim Clothing to Gen Z Fashion Culture on Social Media - Bintang Lutfi R; Nasrulloh Nasrulloh (Penerbit Hellow Pustaka, 2026)
This study analyzes the relationship between ethical principles of dress in the hadith and the modest fashion practices of Generation Z (Gen Z) as exposed on social media platforms, particularly Instagram and TikTok. Building on the strong influence of digital visual culture in shaping Gen Z's religious identity and lifestyle, this study seeks to elaborate on how Islamic sharia values ​​regarding dress etiquette are interpreted, adapted, and implemented within a contemporary aesthetic framework. The method used is an integrated qualitative approach, combining hermeneutical analysis of hadith, visual content analysis, and surveys and digital ethnography. This combination aims to understand behavioral patterns, visual fashion representations, and religious meanings manifested in Gen Z Muslim fashion styles. (Nasrulloh, 2022) Key findings indicate that sharia obligations such as covering the aurat (awrah), avoiding tabarruj (excessive adornment), avoiding syuhrah clothing (clothing of fame), and recommendations for modesty remain essential, but are reinterpreted through digital aesthetics. This modern expression is seen in the adoption of oversized styles, layering techniques, soft hijabi aesthetics, and modest streetwear. Gen Z demonstrates an adaptive attitude; they do not reject religious norms, but rather accommodate them creatively by considering aspects of comfort, personal expression, and the visual demands of social media. Muslim female influencers play a crucial role as mediators who bridge the values ​​of the hadith through compelling narratives and visual imagery. However, ethical challenges arise, such as the phenomenon of hyper-aesthetic modesty and the use of digital filters that have the potential to dilute the essence of modesty. This study concludes that the relationship between sharia and fashion trends is a dynamic process of negotiating meaning, not a contradictory dichotomy. The results of this study are expected to make a significant contribution to the study of visual Islam, the formulation of effective da'wah strategies in the digital space, and the development of a more ethical, relevant, and contextual modest fashion industry for young audiences.